From Perception To Practice: Improving Literacy Pedagogy Through Field-Based Inquiry - Sarah E. Broman (The Advocate, 2017)
For over a century, approaches to reading instruction have been a volatile issue in education. ​The controversy regarding instructional approaches is evidenced in the context of educators’ beliefs regarding developmentally appropriate practice in the classroom. Much has been done in the way of research regarding the relationship between a teacher’s theoretical beliefs and practice in the classroom. However, there is a lack of research surrounding early field experience and the possible influence on preservice teachers’ philosophical viewpoints. The purpose of this study is to explore preservice teachers’ theoretical orientations and how they inform their practices during early field experiences.